Determination of heavy metal concentration of different traditional medicine formulations available at the East Coast Region of Malaysia - Helal Uddin, A.B.M.; Khalid, Reem S.; Abbas, Syed Atif (Academic Journals, 2012)
Traditional medicines (TM) of herbal origin have been increasingly getting popular in the last few decades. In Malaysia, a significant number of people consume locally available traditional medicine for their health care needs. Due to the wide use of herbal medicines, regulatory authorities express concern about the safety of using these products. Heavy metal content of the medicinal formulation is one of them. Exposure to heavy metals may cause many adverse health effects. This study was designed to determine the toxic heavy metals content in locally available traditional medicine in the East Coast Region of Malaysia. Twenty five samples of TM were collected from different places to identify the concentration of five heavy metals namely Zn, Fe, Pb, Cd and Ni. The determination of Zn and Fe were conducted using Flame Atomic Absorption Spectroscopy (FAAS), while Pb, Cd and Ni analysis were conducted using Graphite Furnace Atomic Absorption Spectroscopy (GFAAS). Most of the samples show the presences of those heavy metals with different concentration namely Cd (0.1 to 1.23 ppm), Pb (1.51 to 19.35 ppm), Ni (2.47 to 14.94 ppm), Zn (13.2 to 125 ppm) and Fe (109.4 to 1484.7 ppm